Clinicopathologic Evaluation of Cardiofaciocutaneous Syndrome: Overcoming the Challenges of Diagnosing a Rare Genodermatosis. Issue 1 (16th December 2014) - Bryan, Zachary T.; Missall, Tricia A.; Stieren, Stacy; Siegfried, Elaine; Burkemper, Nicole M.
Abstract We report the case of a 2‐year‐old boy from a family with limited financial resources who presented with cutaneous abnormalities, a history of congenital heart defect, and a presumptive diagnosis of Noonan syndrome. Genetic testing had been deferred because of a lack of funds. Skin findings were characteristic of cardiofaciocutaneous syndrome, including keratosis pilaris, ichthyosis, sparse eyebrows, and multiple nevi. A biopsy of a perifollicular thick papule with background hyperpigmentation was obtained to further characterize the cutaneous findings. Clinical evaluation allowed rapid, cost‐effective, specific diagnosis in this patient with a RASopathy‐spectrum genetic disorder who did not have access to genetic testing. This time‐honored clinical approach is adequate for providing information important for prognosis, follow‐up, and counseling. We will also discuss available resources for genetic testing and specialized care for patients with RASopathies.